2022
DOI: 10.1177/09721509221114679
|View full text |Cite
|
Sign up to set email alerts
|

The Credit Risk of Sustainable Firms during the Pandemic

Abstract: This study investigates how the credit risk of more sustainability-oriented firms changes when national governments intervene in their economies to counterbalance the COVID-19 pandemic. For this reason, we examine how the credit default swap spread changes on a database of all listed firms—for which a credit default swaps (CDS) contract is available—in Europe and the United Kingdom during the whole year of 2020. We find that when national governments intervene in the local economies, the CDS spreads for these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Martínez-Ferrero and García-Sánchez (2017) document that voluntary sustainability disclosures decrease the company's cost of capital and increase the credibility of social responsibility for the company. Similarly, Cardillo and Chiappini (2022) found that sustainable firms absorb policy measures in a better way in comparison to their counterparts as it lessens the credit risks. Cornell (2021) emphasized that companies with high ESG ratings lower the cost of capital, decreasing the investors' expected returns.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Martínez-Ferrero and García-Sánchez (2017) document that voluntary sustainability disclosures decrease the company's cost of capital and increase the credibility of social responsibility for the company. Similarly, Cardillo and Chiappini (2022) found that sustainable firms absorb policy measures in a better way in comparison to their counterparts as it lessens the credit risks. Cornell (2021) emphasized that companies with high ESG ratings lower the cost of capital, decreasing the investors' expected returns.…”
Section: Literature Reviewmentioning
confidence: 93%